Safety and early outcomes after intravenous thrombolysis in acute ischemic stroke patients with prestroke disability. Issue 6 (August 2021) - Cooray, Charith; Karlinski, Michal; Kobayashi, Adam; Ringleb, Peter; Kõrv, Janika; Macleod, Mary J; Dixit, Anand; Azevedo, Elsa; Bladin, Christopher; Ahmed, Niaz
Background: There are limited data on intravenous thrombolysis treatment in ischemic stroke patients with prestroke disability. Aim: We aimed to evaluate safety and outcomes of intravenous thrombolysis treatment in stroke patients with prestroke disability. Methods: We analyzed 88, 094 patients treated with intravenous thrombolysis, recorded in the Safe Implementation of Treatments in Stroke (SITS) International Thrombolysis Register between January 2003 and December 2017, with available NIHSS data at stroke-onset and after 24 h. Of them, 4566 patients (5.2%) had prestroke disability, defined as a modified Rankin Scale score of 3–5. Safety outcome measures included Symptomatic Intracerebral Hemorrhage, any type of parenchymal hematoma on 24 h imaging scans irrespective of clinical symptoms, and death within seven days. Early outcome measures were 24-h NIHSS improvement (≥4 from baseline to 24 h). Results: Patients with prestroke disability were older, had more severe strokes, and more comorbidities than patients without prestroke disability. When comparing patients with prestroke disability with patients without prestroke disability, there was however no significant increase in adjusted odds for symptomatic intracerebral hemorrhage (adjusted odds ratio 0.83 (95% CI 0.60–1.15) (absolute difference in proportion 1.17% vs. 1.27%)) or for parenchymal hemorrhage (adjusted odds ratio 0.96 (0.83–1.11) (7.51% vs. 6.34%)). The prestroke disability group had a significantly lower-adjusted odds ratio for a 24-h NIHSS improvement (adjusted odds ratio 0.79 (0.73–0.85) (45.95% vs. 48.45%)) and a higher adjusted odds ratio for seven-day mortality (aOR 1.40 (1.21–1.61) (10.40% vs. 4.93%)). Conclusions: Intravenous thrombolysis in acute ischemic stroke patients with prestroke disability was not associated with an increased risk of symptomatic intracerebral hemorrhage or parenchymal hemorrhage. Prestroke disability was however associated with a higher risk of early mortality compared to patients without prestroke disability.